Розробка ресурсоощадного очищення промислових стічних вод, які містять сполуки нікелю - Кочетов, Г.М.; Сімоніч, М. (Екологічна безпека та природокористування, 2012)
A comprehensive ion-exchange based technological scheme is proposed for treatment of nickel-containing wastewater. The new environmentally sound method for utilisation of eluates of ion-exchange filters with production of a ferromagnetic material is developed.